Lessons learned from inter-laboratory studies of carbon isotope analysis of honey. Issue 1 (January 2019) - Dunn, Philip J.H.; Hill, Sarah; Cowen, Simon; Goenaga-Infante, Heidi; Sargent, Mike; Gören, Ahmet Ceyhan; Bilsel, Mine; Şimşek, Adnan; Ogrinc, Nives; Potočnik, Doris; Armishaw, Paul; Hai, Lu; et al.
Abstract: Forensic application of carbon isotope ratio measurements of honey and honey protein to investigate the degree of adulteration with high fructose corn syrup or other C4 plant sugars is well established. These measurements must use methods that exhibit suitable performance criteria, particularly with regard to measurement uncertainty and traceability – low levels of adulteration can only be detected by methods that result in suitably small measurement uncertainties such that differences of 1‰ or less can be reliably detected. Inter-laboratory exercises are invaluable to assess the state-of-the art of measurement capabilities of laboratories necessary to achieve such performance criteria. National and designated metrology institutes from a number of countries recently participated in an inter-laboratory assessment (CCQM-K140) of stable carbon isotope ratio determination of bulk honey. The same sample material was distributed to a number of forensic isotope analysis laboratories that could not participate directly in the metrological comparison. The results from these studies have demonstrated that the majority of participants provided isotope delta values with acceptable performance metrics; that all participants ensured traceability of their results; and that where measurement uncertainties were reported; these were fit-for-purpose. A number of the forensic laboratories only reported precision rather than full estimates of measurement uncertainty and this was the major cause of the few instances of questionable performance metrics. Reporting of standard deviations in place of measurement uncertainties is common practice outside metrology institutes and the implications for interpretations of small differences in isotopic compositions are discussed. The results have also highlighted a number of considerations that are useful for organisers of similar inter-laboratory studies in the future. Highlights: International comparison with national institutes confirms forensic laboratory data. ILC protocols should specify minimum sample amount for isotope ratio analysis. Isotope analysis laboratories should report measurement uncertainties. Measurement uncertainties should include contributions from all data corrections. Measurement uncertainties should be considered when evaluating ILC performance.